Retracted: Selection of intermediate routes for secure data communication systems using graph theory application and grey wolf optimization algorithm in MANETs. Issue 5 (5th May 2021) - Balaji, Subbiah; Obaidat, Mohammad S.; Suthir, Sriram; Rajesh, Manoharan; Suresh, Koneri Chandrasekaran
Abstract: Retraction: "Selection of intermediate routes for secure data communication systems using graph theory application and grey wolf optimization algorithm in MANETs" by authors Subbiah Balaji, Mohammad S. Obaidat, Sriram Suthir, Manoharan Rajesh and Koneri Chandrasekaran Suresh, IET Netw. 2021;1–7. https://doi.org/10.1049/ntw2.12026 . The above article, published online on 5 May 2021 in Wiley Online Library (wileyonlinelibrary.com ), has been retracted by agreement between the journal Editor‐in‐Chief, Han‐Chieh Chao and John Wiley and Sons Ltd. The retraction has been agreed due to evidence indicating that the peer review of this paper was compromised.